Corpo spirituale e Terra celeste: Dall'Iran mazdeo all'Iran sciite - Corbin, Henry; Bemporad, Gabriella (Milan Adelphi, 2002)
When it appeared in its first version (1960), this book sounded like a bewildering attempt to link and articulate categories of remote Mazdean Iran, encrypted and difficult, with others of Shiism, about which very little was known. Today, one can say of Corpo spirituale e Terra celeste that it was a true starting point, but not only for the audacity of the historical perspective. Essential here is the elaboration of a conception of the imagination that many later drew on for its grandeur and perspicuity. Here, a 'map of the Imaginal' is drawn for the first time. To understand the novelty of the enterprise, one need only think that the word 'imaginal' itself was introduced by Corbin. And a new word was indeed needed since, in the West, "between sensible perceptions and the intuitions or categories of the intellect the place had remained empty". This was precisely the place of the true Imaginatio of alchemy, of active imagination, of that "interworld between the sensible and the intelligible" whose "disappearance brings with it a catastrophe of the Spirit". That place of knowledge, and of a knowledge precluded to us, is the "eighth climate" where the mystical cities of Jābalqā, Jābarsā and Hūrqalyā appear. No civilisation has been equal to the Iranian one in developing this 'imaginal geography'. From the admirable landscapes, pure archetypes of a visionary nature, to the exhilarating pages of Sohravardī or Mollā Sadrā, Iran has offered us the most detailed guide to the 'Land of Hūrqalya', 'the world through which spirits are corporealised and bodies spiritualised', the place of epiphanic reality. Until this book by Corbin, very little had filtered through of such treasures - and the second part of the work also offers us a rich anthology of Iranian texts on these themes, translated for the first time. But the subversive effect of Corpo spirituale as a whole is not only due to the novelty of the materials. Here we witness, first and foremost, the unfolding of Corbin's perspective. The author himself called it 'phenomenological', in contrast to all historicism. But, rather than Western terms, one should refer, in order to define Corbin's procedure, to that "hermeneutics par excellence indicated by the word ta'wīl, which literally means 'leading a thing back to its source', to its archetype, to its true reality". Here the ta'w īl is both the object of the book and the method of its author, as it should also become the path of every reader. Thus we will finally approach the Tree of Imagination, of which the Qur'ān says that it can be "the blessed Tree" or "the cursed Tree". "The imaginal can be harmless; the imaginal never is". (Translated with DeepL.com)
Includes bibliographical references and index.
First ed. published in 1960 under title: Terre céleste et corps de résurrection.
Keywords: Sufism; Philosophy; Iran